Neurohypophyseal Hormone-Sensitive Adenyl Cyclase of Toad Urinary Bladder - Bär, Hans-Peter (1970)
An adenyl cyclase preparation derived from epithelial cells of the urinary bladder of the toad, Bufo marinus, is described. This cyclase preparation is specifically stimulated by neurohypophyseal hormones and various synthetic analogs which evoke a hydroosmotic response in the intact bladder. The relative stimulatory effects of these compounds have been compared on the cyclase preparation and in the intact bladder. The peptide concentrations required for half-maximal stimulation (affinity) in the cell-free and intact systems were parallel; however the magnitude of stimulation produced by saturating concentrations of peptides did not correlate. Furthermore, it was found that peptide analogs which inhibit the hydroosmotic effect of [8-arginine]-vasopressin on the intact bladder also inhibit the stimulation of the toad bladder cyclase preparation by vasopressin. Prostaglandin E(1), mercaptans, and disulfides, which inhibit the hormone-induced hydroosmotic response of the intact bladder, did not antagonize the stimulation of the toad bladder cyclase preparation by vasopressin.